Stigmatization and social discrimination of pulmonary tuberculosis patients in Kotamobagu City, North Sulawesi: A qualitative study - Akbar, Hairil; Kamaruddin, Syamsu A.; Adam, Arlin (Svāsthya: Trends in General Medicine and Public Health, 2025)
Tuberculosis (TB) remains a significant public health challenge, particularly in developing countries such as Indonesia. In Kotamobagu city, North Sulawesi, despite being recognized as one of Indonesia's most tolerant cities, patients with TB face persistent stigmatization and discrimination.  This study aimed to examine the social construction of discrimination against TB patients in Kotamobagu city, focusing on how these perceptions develop and persist. This qualitative study employed a constructivist paradigm and utilized Berger and Luckman's social construction theory. Data were collected through in-depth interviews and direct observations of 16 informants, including patients with TB, healthcare workers, family members, neighbors, and colleagues. The analysis was conducted via NVIVO 12 Plus software following a systematic thematic approach. The study revealed complex patterns of stigmatization and discrimination across familial, community, and workplace settings. Network analysis revealed interconnected stigmatization factors, with physical isolation emerging as a primary preventive reaction within families. Social distancing behaviors have been documented in both familial and workplace environments. This research identified multiple pathways through which stigmatization affects patients' lives, including social isolation, psychological impact, and treatment adherence. Fear of transmission has emerged as the primary driver of discriminatory behaviors, leading to various forms of social exclusion and workplace ostracism. TB-related stigma and discrimination in Kotamobagu manifest through complex social mechanisms that significantly affect patients' psychological well-being and treatment outcomes. These findings emphasize the need for comprehensive interventions that address both the structural and interpersonal aspects of stigma, particularly in workplace and family settings.